Effectiveness of Physical Activity in the Management of Nonspecific Low Back Pain: A Systematic Review - Alexandra Alonso-Sal; José Luís Alonso-Perez; María Dolores Sosa-Reina; Juan Antonio García-Noblejas-Fernández; Viren Gul Balani-Balani; Giacomo Rossettini; Jorge Hugo Villafañe (Medicina)
Background and Objectives: This systematic review evaluates the effectiveness of exercise interventions for managing nonspecific low back pain (NSLBP) and explores their impact on related biopsychosocial factors, physical health variables, and inflammatory biomarkers. Materials and Methods: A comprehensive search of five databases (PubMed, CINAHL, PEDro, SCOPUS, Cochrane Library) was conducted, covering studies from 2019 to 2024. Fifteen randomized controlled trials involving 1338 participants aged 18 to 65 years with NSLBP were included. Data extraction and quality assessment were performed independently by two reviewers using the PEDro scale, and risk of bias was evaluated using the Cochrane Risk-of-Bias tool (RoB 2.0). Results: Exercise significantly reduced pain intensity and improved biopsychosocial factors such as depression, disability, functionality, quality of life, and kinesiophobia. Additionally, it enhanced physical parameters like proprioception, muscle thickness, and physical performance. However, the review found insufficient evidence regarding the effects of exercise on inflammatory biomarkers in NSLBP patients. Conclusions: The findings suggest that physical exercise is an effective intervention for pain reduction and the improvement of overall health in NSLBP, though further research is needed to clarify its impact on inflammation.